2015
DOI: 10.3126/saarctb.v11i2.12435
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Diagnosis of Tuberculosis among Under Treatment Patients in Rajshahi City, Bangladesh

Abstract: Introduction: Delay in diagnosis regarding Tuberculosis (TB) is common in developing country as well as in Bangladesh. Therefore, the aim of the study is to identify the factors which have effects on delay in diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Patients who lived more than 10 kilometers away from a health institution were more likely to delay more than 5 weeks in getting an EPTB diagnosis. Similar studies also reported the association between long-distance and delay of EPTB diagnosis [ 9 , 27 ]. This implies that limited accessibility of healthcare facilities could affect the implementation of TB programs and could delay the diagnosis of potentially infectious pulmonary TB [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 61%
“…Patients who lived more than 10 kilometers away from a health institution were more likely to delay more than 5 weeks in getting an EPTB diagnosis. Similar studies also reported the association between long-distance and delay of EPTB diagnosis [ 9 , 27 ]. This implies that limited accessibility of healthcare facilities could affect the implementation of TB programs and could delay the diagnosis of potentially infectious pulmonary TB [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 61%
“…Delays in TB diagnosis were also high in the Amhara region, with three-fifths of patients having delays in TB diagnosis and treatment [ 24 ]. The lack of appropriate intervention was the main contributor to the delay in TB diagnosis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this success, some patients continue to refuse, delay, or do not adhere to TB treatments [ 13 , 14 ]. The anthropologist Paul Mason said that one must go beyond the medical model of TB and acknowledge the socio-economic and cultural aspects of the disease to ensure its effective treatment and prevention [ 15 ].…”
Section: Introductionmentioning
confidence: 99%